Down‐regulation of tissue N:P ratios in terrestrial plants by elevated CO2. Issue 12 (1st December 2015) - Deng, Qi; Hui, Dafeng; Luo, Yiqi; Elser, James; Wang, Ying-Ping; Loladze, Irakli; Zhang, Quanfa; Dennis, Sam
Abstract : Increasing atmospheric CO2 concentrations generally alter element stoichiometry in plants. However, a comprehensive evaluation of the elevated CO2 impact on plant nitrogen : phosphorus (N:P) ratios and the underlying mechanism has not been conducted. We synthesized the results from 112 previously published studies using meta‐analysis to evaluate the effects of elevated CO2 on the N:P ratio of terrestrial plants and to explore the underlying mechanism based on plant growth and soil P dynamics. Our results show that terrestrial plants grown under elevated CO2 had lower N:P ratios in both above‐ and belowground biomass across different ecosystem types. The response ratio for plant N:P was negatively correlated with the response ratio for plant growth in croplands and grasslands, and showed a stronger relationship for P than for N. In addition, the CO2 ‐induced down‐regulation of plant N:P was accompanied by 19.3% and 4.2% increases in soil phosphatase activity and labile P, respectively, and a 10.1% decrease in total soil P. Our results show that down‐regulation of plant N:P under elevated CO2 corresponds with accelerated soil P cycling. These findings should be useful for better understanding of terrestrial plant stoichiometry in response to elevated CO2 and of the underlying mechanisms affecting nutrient dynamics under climate change.